Jewish Life as the Main Theme of Saul Bellow’s Novels - Sinha, Arti (Journal of Advanced Research in English & Education, 2021)
As the most influential contemporary American literary figure, Saul Bellow is the true picture of confusion and spiritual emptiness of western society. He, in his literary career, wrote a large number of novels, which won several awards including ‘Nobel Prize’. In his novels, Bellow explores modern living condition. He depicts urban intellectuals, especially the plight of American-Jewish intellectuals and is concerned about the real need and aspirations of the modern man. How to cite this article:  Sinha A. Jewish Life as the Main Theme of Saul Bellow’s Novels. J Adv Res Eng & Edu 2019; 4(4): 6-8. DOI: https://doi.org/10.24321/2456.4370.201908